Socially adaptive belief. (16th April 2020) - Williams, Daniel
Abstract : I clarify and defend the hypothesis that human belief formation is sensitive to social rewards and punishments, such that beliefs are sometimes formed based on unconscious expectations of their likely effects on other agents – agents who frequently reward us when we hold ungrounded beliefs and punish us when we hold reasonable ones. After clarifying this phenomenon and distinguishing it from other sources of bias in the psychological literature, I argue that the hypothesis is plausible on theoretical grounds and I show how it illuminates and unifies a range of psychological phenomena, including confabulation and rationalisation, positive illusions, and identity‐protective cognition.